The switch triggering the invasion process: Lipid metabolism in the metastasis of hepatocellular carcinoma - Jiaqian Zhang; Zhicheng Zhang; Zhangfan Wu; Yufei Wang; Zerui Zhang; Limin Xia; Yuanyuan Ji (Chinese Medical Journal, 2024)
Abstract. In humans, the liver is a central metabolic organ with a complex and unique histological microenvironment. Hepatocellular carcinoma (HCC), which is a highly aggressive disease with a poor prognosis, accounts for most cases of primary liver cancer. As an emerging hallmark of cancers, metabolic reprogramming acts as a runaway mechanism that disrupts homeostasis of the affected organs, including the liver. Specifically, rewiring of the liver metabolic microenvironment, including lipid metabolism, is driven by HCC cells, propelling the phenotypes of HCC cells, including dissemination, invasion, and even metastasis in return. The resulting formation of this vicious loop facilitates various malignant behaviors of HCC further. However, few articles have comprehensively summarized lipid reprogramming in HCC metastasis. Here, we have reviewed the general situation of the liver microenvironment and the physiological lipid metabolism in the liver, and highlighted the effects of different aspects of lipid metabolism on HCC metastasis to explore the underlying mechanisms. In addition, we have recapitulated promising therapeutic strategies targeting lipid metabolism and the effects of lipid metabolic reprogramming on the efficacy of HCC systematical therapy, aiming to offer new perspectives for targeted therapy.